Magí Murià, periodista i cineasta : "memòries d'un exiliat, 1939-1948" / Joaquim Romaguera i Ramió ; pròleg de José María Murià i Rouret - Muriá, José María (1942-); Romaguera i Ramió, Joaquim (Col.lecció Guimet ; 55)
Bibliografías. Índices